2013
DOI: 10.3390/s130810167
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Molar Deltamethrin Sensor Based on Electrical Impedance of PAH/PAZO Layer-by-Layer Sensing Films

Abstract: This work reports a novel deltamethrin (DM) sensor able to detect nano-molar concentrations in ethanol solutions. The sensing layer consists of a thin film, obtained via a layer-by-layer technique, from alternate adsorption of poly(allylamine chloride) (PAH) and poly[1-[4-(3-carboxy-4-hydroxyphenylazo)-benzenesulfonamide)-1,2-ethanediyl]sodium salt] (PAZO) onto a solid support with interdigitaded gold electrodes. The sensor response, obtained from impedance spectroscopy measurements, was revealed to be linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…TCS is one of the most studied pollutants in sensors development, as examples: a strand of carbon fibers with a voltammetric detector for high-performance liquid chromatography to detect TCS in rabbit serum and urine [32]; an electropolymerizing o-phenylenediamine on a glassy carbon electrode, using an amperometric sensor achieved a linear range of 2.0 × 10 −7 -3.0 × 10 −6 mol/L and a detection limit of 8.0 × 10 −8 mol/L [22]; a multiwall carbon nanotube film was developed for TCS detection using a electrochemical sensor with a linear range from 50 to 1.75 mg L −1 , and a limit of detection of 16.5 µg L −1 (57 nM) [33]. Recent studies [34][35][36][37][38] have reported well succeeded applications with sensors composed of layer-by-layer (LbL) thin-films, which were produced with polyelectrolytes and used to detect organic compounds (in ultrapure water matrices and methanol) using impedance measurements.…”
Section: Introductionmentioning
confidence: 99%
“…TCS is one of the most studied pollutants in sensors development, as examples: a strand of carbon fibers with a voltammetric detector for high-performance liquid chromatography to detect TCS in rabbit serum and urine [32]; an electropolymerizing o-phenylenediamine on a glassy carbon electrode, using an amperometric sensor achieved a linear range of 2.0 × 10 −7 -3.0 × 10 −6 mol/L and a detection limit of 8.0 × 10 −8 mol/L [22]; a multiwall carbon nanotube film was developed for TCS detection using a electrochemical sensor with a linear range from 50 to 1.75 mg L −1 , and a limit of detection of 16.5 µg L −1 (57 nM) [33]. Recent studies [34][35][36][37][38] have reported well succeeded applications with sensors composed of layer-by-layer (LbL) thin-films, which were produced with polyelectrolytes and used to detect organic compounds (in ultrapure water matrices and methanol) using impedance measurements.…”
Section: Introductionmentioning
confidence: 99%
“…At acidic pH, TCS is nearly non-dissociated, hence an improved adsorption capacity was observed due to the increase of attractive interactions on the PAH layer (H-bond formation and hydrophobic interaction) [2, and references therein]. In addition, since protonated TCS molecules are more hydrophobic than the deprotonated anions, increased adsorption is likely to occur on the PAH and PVS layers at lower pH [10,11]. It is important to note that the highest absorbances of TCS onto (PAH/PVS) 10 /PAH and (PAH/PVS) 10 both at 232 nm and 280 nm were at pH 5.68 and 3.7, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of pollutant traces is crucial for guaranteeing the safety of public water supply and aquifers, which can be contaminated by pesticides [1], industrial products, personal hygiene pharmaceutical products (PPCPs) [2][3][4][5], and other emerging contaminants [6]. Among the latter contaminants, attention has been paid to plastic packaging containing bisphenol A (2,2-bis (4-hydroxyphenyl) propane) (BPA), a poorly water-soluble compound (5.2 × 10 −4 mol L -1 ) used in manufacturing [7] of polycarbonate plastics and epoxy resins [4,8,9].…”
Section: Introductionmentioning
confidence: 99%